CHANGES IN THE INTESTINAL MICROBIOTA IN PATIENTS WITH ULCERATIVE COLITIS AND IRRITABLE BOWEL SYNDROME COMBINED WITH UROLITHIASIS - Kyrian, O.A.; Derkach, I.A.; Dorofeyev, A.E.; Rudenko, M.M. (World of Medicine and Biology, 2021)
The paper is devoted to the study of changes in the intestinal microbiome in patients with urolithiasis that occurred against the background of ulcerative colitis and irritable bowel syndrome. It was found that about 20 % of patients with urolithiasis have symptoms of irritable bowel syndrome, with more than half of the stones consisting of oxalates. In the study of fecal microflora in patients with the method of sequencing of the 16S gene of ribosomal RNA, compared with healthy, a significant decrease in Firmicutes, Faecalibacterium prausnitzii, Akkermansia muciniphila and the Firmicutes/Bacteroidetes ratio was revealed. The detected changes in the microflora can be associated both with direct changes in the intestine, inherent in nonspecific ulcerative colitis and irritable bowel syndrome, and with more frequent use of uroseptics/antibiotics in this category of patients.
Keywords: urolithiasis; fecal microflora; phylotypes; intestinal diseases